Understanding knowledge management and information management: the need for an empirical perspective - France Bouthillier; Kathleen Shearer (Information Research: An International Electronic Journal)
It has been argued that Knowledge Management (KM) is not a new field but a different way to refer to Information Management (IM). This article seeks to summarize empirical evidence of how KM is practiced in several types of organizations to show the variety of organizational approaches that are used and the processes that are involved. Based on an exploratory study of KM practices, the article presents a typology of methodologies that are employed in various organizations, to help illustrate the particular nature of KM and show that it is substantially different from IM. In the first part of the article, the concepts associated with the management of information and knowledge are examined and definitions of IM and KM are presented to clarify their differences. The second part of the article  contains the a description of the conceptual framework used for the study and a presentation and discussion of  the results.